Physical properties of pulsed laser ablation and chemical vapour deposition synthesised carbon nanospheres - Mouane, Othmane (My University, 2021)
Monodispersed and uniform carbon nanospheres with a diameter in the range of 40-50 nm were synthesised with a new and fast laser based developed technique. The synthesis method consisted of the irradiation of Highly Oriented Pyrolytic Graphite (HOPG) sample by an ultraviolet pulsed laser with power densities in the order of 108 W.cm-2 under the presence of hydrogen gas. The morphological and elemental characterisation carried with Scanning Electron Microscopy revealed the existence of two different regions within a shockwave generated at the irradiated spots and the formation of pure carbon nanostructures with spherical shape. Raman line-scans confirmed the nano-structuration of the HOPG surfaces and the appearance of carbon nanospheres at the shockwave regions. The detailed study of different parameters which influenced the growth process allowed the uncovering of the optimum conditions at which the formed carbon nanospheres were of high quality and of high production rate. It was found that the fluence threshold and the hydrogen presence were crucial for the formation of these carbon nanospheres. In addition, the critical thermodynamic parameters (pressure and temperature) generated by the pulsed laser were calculated. This provided a better insight regarding the phase transformation of HOPG from a macro to a nano-structure and the nucleation process which leads to the formation of carbon nanospheres. The second part of this work focused on investigating the magnetic and electric properties of different carbon nanospheres synthesised by chemical vapour deposition, using a state of the art physical property measurement system (PPMS). Scanning electron microscopy imaging of the two investigated sets of carbon nanospheres, grown under slightly different conditions, revealed a difference in size with diameters of about 200 and 400 nm respectively. Induced coupled plasma mass spectroscopy showed the presence of ferromagnetic impurities such as Fe, and Ni at concentration levels less than 120 and 3 ppm respectively. PPMS magnetic measurements of the two samples showed two different characteristics. In Sample “A”, with nanospheres of about 200 nm in diameter, clear ferromagnetism behaviour was observed, while in sample “B”, diamagnetic behaviour was observed except at low temperature (>10 K), at which clear superparamagnetic behaviour is observed. The electrical measurements on a network of carbon nanospheres of sample “A” revealed a semiconductor characteristic and showed a variable range hopping class of conductivity in agreement with work conducted on carbon nanotubes networks
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2021